Surgical management of supracondylar femur fracture using rush pinning technique in dogs - KUMAR, AKSHAY; KUMAR, AMIT; RANA, YUDHVIR; KAUSHAL, SARA; KUMAR, ROHIT; TYAGI, S P; KUMAR, ADARSH; NAGPAL, AHAN (The Indian Journal of Animal Sciences, 2024)
Supracondylar femur fracture in twelve dogs were managed using rush pinning technique. Post-operative radiographs displayed good anatomical alignment and reduction of fracture fragments without any pin migration. All the eight dogs showed normal gait without any limp on last reappraisal day. Rush pinning yielded good clinical outcomes in the management of supracondylar femur fractures with minimum complications.